Cryptic habitat use of white sharks in kelp forest revealed by animal-borne video. (3rd April 2019) - Jewell, Oliver J. D.; Gleiss, Adrian C.; Jorgensen, Salvador J.; Andrzejaczek, Samantha; Moxley, Jerry H.; Beatty, Stephen J.; Wikelski, Martin; Block, Barbara A.; Chapple, Taylor K.
Abstract : Traditional forms of marine wildlife research are often restricted to coarse telemetry or surface-based observations, limiting information on fine-scale behaviours such as predator–prey events and interactions with habitat features. We use contemporary animal-attached cameras with motion sensing dataloggers, to reveal novel behaviours by white sharks, Carcharodon carcharias, within areas of kelp forest in South Africa. All white sharks tagged in this study spent time adjacent to kelp forests, with several moving throughout densely kelp-covered areas, navigating through channels and pushing directly through stipes and fronds. We found that activity and turning rates significantly increased within kelp forest. Over 28 h of video data revealed that white shark encounters with Cape fur seals, Arctocephalus pusillus pusillus, occurred exclusively within kelp forests, with seals displaying predator evasion behaviour during those encounters. Uniquely, we reveal the use of kelp forest habitat by white sharks, previously assumed inaccessible to these large predators.